Prognostic values of D816V KIT mutation and peri-transplant CBFB-MYH11 MRD monitoring on acute myeloid leukemia with CBFB-MYH11 - Cho, Byung-Sik; Min, Gi-June; Park, Sung-Soo; Park, Silvia; Jeon, Young-Woo; Shin, Seung-Hwan; Yahng, Seung-Ah; Yoon, Jae-Ho; Lee, Sung-Eun; Eom, Ki-Seong; Kim, Yoo-Jin; Lee, Seok; et al. (Bone marrow transplantation (Basingstoke), 2021)
Given the controversies in the prognostic value of KIT mutations and optimal thresholds and time points of MRD monitoring for AML with CBFB-MYH11 , we retrospectively evaluated 88 patients who underwent allogeneic hematopoietic stem cell transplantation (Allo-HSCT, n = 60) or autologous HSCT (Auto-HSCT, n = 28). The D816V KIT mutation was significantly associated with post-transplant relapse, contrasting with other types of mutations in KIT . Pre- and post-transplant (3 months after transplant) CBFB-MYH11 MRD assessments were useful in predicting post-transplant relapse and poor survival. The optimal threshold was determined as a 2 log reduction at both time points. In multivariate analysis, the D816V KIT mutation and CBFB-MYH11 MRD assessments were independently associated with post-transplant relapse and survival. Stratification by D816V KIT and pre-transplant CBFB-MYH11 MRD status further distinguished the risk of relapse and survival. Auto-HSCT was superior to Allo-HSCT in MRD negative patients without D816V KIT , while Allo-HSCT trended to be superior to Auto-HSCT in patients with MRD positivity or the D816V KIT mutation. In conclusion, this study demonstrated the differentiated prognostic value of the D816V KIT mutation in AML with CBFB-MYH11 and clarified optimal time points and thresholds for CBFB-MYH11 MRD monitoring in the setting of HSCT.